1998
DOI: 10.1007/s002689900479
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis in Liver Transplant Donors: Common Feature of Donor Population?

Abstract: Fatty change in donor livers is a risk factor for poor function after orthotopic liver transplantation. Various prevalences of steatosis have been reported in time 0 biopsies. The aim of this research was to determine, in a longitudinal study, the degree (percent of hepatocytes involved) and type (size of vacuoles) of fatty change shown by various histologic techniques. Four staining methods were used on sections from three liver wedge biopsies—at liver procurement, at the back‐table, and after reperfusion—fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Triglycerides are synthesized from FFA and can be stored in lipid droplets or packed as VLDL particles for export to extrahepatic organs. Although previous studies have addressed the impact of qualitative steatosis (macrovesicular vs. microvesicular) to hepatic I/R injury [3][4][5][6][7], no studies have compared side-by-side the specific contribution of the individual lipids accumulating in fatty liver to I/R injury. In order to discern whether the type rather than the amount of fat contributes to the susceptibility of fatty livers to I/R injury, we used nutritional models of hepatic steatosis characterized by predominant TG/FFA or cholesterol accumulation by feeding a diet deficient in choline or enriched in cholesterol, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triglycerides are synthesized from FFA and can be stored in lipid droplets or packed as VLDL particles for export to extrahepatic organs. Although previous studies have addressed the impact of qualitative steatosis (macrovesicular vs. microvesicular) to hepatic I/R injury [3][4][5][6][7], no studies have compared side-by-side the specific contribution of the individual lipids accumulating in fatty liver to I/R injury. In order to discern whether the type rather than the amount of fat contributes to the susceptibility of fatty livers to I/R injury, we used nutritional models of hepatic steatosis characterized by predominant TG/FFA or cholesterol accumulation by feeding a diet deficient in choline or enriched in cholesterol, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the contribution of microvesicular steatosis to graft dysfunction after transplantation remains unclear. For instance, while some studies showed that livers with moderate microsteatosis are nonfunctional after transplantation [5], other reports discarded a role for microvesicular steatosis on graft or patient survival [6,7]. Hence, a better understanding of the mechanisms involved in the susceptibility of fatty livers to I/R injury may increase the availability of donor organs, providing a better chance for liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Far greater levels of steatosis have been identified using specific fat stains by other groups. 7,9,16 Markin et al, 9 using Oil red O, found steatosis in 51% of 187 livers. However, the investigators dismissed this figure because, in their opinion, this staining technique was unreliable for fatty change, staining sinusoids as well as vacuoles.…”
Section: Incidencementioning
confidence: 99%
“…Another series of 83 consecutive liver wedge biopsy specimens obtained at liver procurement, on the backbench, and after reperfusion showed greater than 30% steatosis in 49% of sections stained with toluidine blue solution (TBS). 7 …”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation